Status of E-government and Public Service Delivery in Nepal - Chalaune, Tirth Bahadur (Karnali Outlook: Knowledge Across Disciplines, 2026)
E-government represents an Innovative use of ICT, internet, and web technologies to deliver public services, enhance transparency, and participation through models like G2C, G2B, G2E, and G2G. In Nepal, a federal, landlocked nation with diverse topography and a literacy rate of 76.3%, e-government holds promise for overcoming inefficiencies in public service delivery persistent challenges like political instability and digital divides. Despite gradual improvements, evidenced by Nepal’s EGDI rank rising from 165th in 2014 to 119th in 2024 and fluctuating EPI performance, this progress lags behind SAARC peers, highlighting gaps in online services, infrastructure, and human capital index. Key research questions address current status and impacts, historical developments, and implementation challenges. Employing an exploratory research design with descriptive analysis, the study relies on secondary data from UN E-Government Surveys, government reports, and national policies. A Comparative Analysis Model evaluates Nepal’s EGDI/EPI against SAARC countries and tracks year-wise trends. Findings reveal strengths in telecom infrastructure but underscore barriers like low literacy, weak coordination, and infrastructure deficits, alongside success factors such as capacity building and monitoring. Recommendations emphasize citizen-centric reforms to elevate Nepal’s e-governance.